Are caffeine effects equivalent between different modes of administration: the acute effects of 3 mg.kg−1 caffeine on the muscular strength and power of male university Rugby Union players - Jason Tallis; Michael, J. Duncan; Neil, D. Clarke; Rhys O. Morris; Ryan, A. Tamilio (Journal of the International Society of Sports Nutrition)
Background There is growing interest in the potential of alternative modes of caffeine administration for enhancing sports performance. Given that alternative modes may evoke improved physical performance via distinct mechanisms, effects may not be comparable and studies directly comparing the erogenicity of alternative modes of caffeine administration are lacking. To address this knowledge gap, the present study evaluated the effect of 3 mg·kg−1 caffeine delivered in anhydrous form via capsule ingestion, chewing gum or mouth rinsing on measures of muscular strength, power, and strength endurance in male Rugby Union players.Methods Twenty-seven participants completed the study (Mean ± SD: Age 20 ± 2 yrs; daily caffeine consumption 188 ± 88 mg). Following assessments and reassessment of chest press (CP), shoulder press (SP), Deadlift (DL), and Squat (SQ) 1-repetition maximum (1RM) and familiarization to the experimental procedures, participants completed six experimental trials where they were administered 3 mg.kg−1 caffeine (Caff) or placebo (Plac) capsule(CAP), chewing gum(GUM) or mouth rinse(RINSE) in a randomized, double-blind and counterbalanced fashion prior to force platform assessment of countermovement jump, drop jump and isometric mid-thigh pull performance. Strength endurance was measured across two sets of CP, SP, DL, and SQ at 70% 1RM until failure. Pre-exercise perceptions of motivation and arousal were also determined.Results Caffeine increased perceived readiness to invest mental effort (p = .038; ηp2=.156), countermovement jump height (p = .035; ηp2=.160) and SQ repetitions until failure in the first set (p < .001; d = .481), but there was no effect of delivery mode (p > .687; ηp2<.015). Readiness to invest physical effort, felt arousal, drop jump height, countermovement jump, drop jump and isometric mid-thigh pull ground reaction force-time characteristics and repetitions until failure in CP, SP and DL were not affected by caffeine administration or mode of caffeine delivery (p > .0.052; ηp2< .136).Conclusion 3 mg.kg−1 caffeine administered via capsule, gum or mouth rinse had limited effects on muscular strength, power, and strength endurance. Small effects of caffeine on CMJ height could not be explained by changes in specific ground reaction force-time characteristics and were not transferable to DJ performance, and effects specific to the SQ RTP exercise underpin the complexity in understanding effects of caffeine on muscular function. Novel modes of caffeine administration proposed to evoke benefits via distinct mechanisms did not offer unique effects, and the small number of effects demonstrated may have little translation to a single performance trial when data examining direct comparison of each caffeine vehicle compared against a mode matched placebo is considered.